Analysis of factors affecting the satisfaction of using Aisyah BSI Chatbot using UTAUT 2 Theory - Isnaini , Hasna Hanifah; Tulasmi, Tulasmi (Universitas Islam Indonesia, 2024)
IntroductionChatbots have become an integral part of digital banking, offering seamless and efficient customer service. However, their adoption in Islamic banking raises unique challenges, particularly in fostering user satisfaction and loyalty, as emotional and personal connections are often limited.ObjectivesThis study analyzes the factors influencing user satisfaction and adoption of the Aisyah BSI chatbot, employing the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2). The study explores constructs such as habit, behavioral intention, and use behavior, offering insights into their roles in shaping user engagement.MethodA quantitative approach was adopted, utilizing a structured questionnaire to collect data from 68 respondents who were users of the Aisyah BSI chatbot. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to test the relationships among variables, including performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, habit, behavioral intention, and use behavior.ResultsThe findings reveal that habit significantly influences behavioral intention, and behavioral intention mediates the relationship between habit and use behavior. Conversely, constructs such as performance expectancy, effort expectancy, social influence, and price value showed no significant impact on behavioral intention or use behavior. The model demonstrated a good fit, with an SRMR value of 0.094.ImplicationsThe study highlights the importance of fostering habitual use and strengthening behavioral intention to enhance user satisfaction with banking chatbots. These findings provide actionable recommendations for improving chatbot design and strategy, particularly in the Islamic banking sector.Originality/NoveltyThis research extends the application of the UTAUT 2 framework to a culturally specific context, contributing to the theoretical understanding of chatbot adoption in Islamic banking and offering practical insights for enhancing user engagement.